2003
DOI: 10.1007/s00422-003-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Conduction in bundles of demyelinated nerve fibers: computer simulation

Abstract: This study presents a model of action potential propagation in bundles of myelinated nerve fibers. The model combines the single-cable formulation of Goldman and Albus (1967) with a basic representation of the ephaptic interaction among the fibers. We analyze first the behavior of the conduction velocity (CV) under the change of the various conductance parameters and temperature. The main parameter influencing the CV is the fast sodium conductance, and the dependence of CV on the temperature is linear up to 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 21 publications
4
65
0
3
Order By: Relevance
“…There is no evidence for this yet, but modelling studies indicate that the relative location of nodes of Ranvier on two adjacent myelinated axons might also determine the degree of temporal synchrony between fibres 113,114 . On small unmyelinated axons, ephaptic interaction between axons is predicted to be minimal 115 but future research might reveal a powerful means to thoroughly synchronize neuronal activity downstream of the site of action potential initiation.…”
Section: Axo-axonal Coupling and Fast Synchronizationmentioning
confidence: 99%
“…There is no evidence for this yet, but modelling studies indicate that the relative location of nodes of Ranvier on two adjacent myelinated axons might also determine the degree of temporal synchrony between fibres 113,114 . On small unmyelinated axons, ephaptic interaction between axons is predicted to be minimal 115 but future research might reveal a powerful means to thoroughly synchronize neuronal activity downstream of the site of action potential initiation.…”
Section: Axo-axonal Coupling and Fast Synchronizationmentioning
confidence: 99%
“…However, for long stimuli train, [Na + ] in variations may not be negligible. In our model, the persistent A-current strongly maintain the membrane between myelinated nerve fibers [35,36] must be modeled.…”
Section: Discussionmentioning
confidence: 99%
“…The work [20,21] considers two types of coupling at once, ephaptic and ohmetric, and that approach may provide further insight into the dynamics of our present problem. The work in [3] is concerned with ephaptic coupling in nonmyelinated nerve fibers that might be modeled with (1.1) with large D. In [16], the authors focus on the effects of demyelination of nerve fibers in large bundles and observe a reduction in the speed of action potential propagation when the nodes of Ranvier are aligned. In addition, we have shown that for any value of A, there is a value of β such that a 1 = a 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Although our particular model is motivated by this neurological application, similar models may also be used to study action potentials in cardiac cells, among other things (see [3,16,20,21]). The authors in [1] also mention the possible application of coupled two-dimensional lattices to the study of image processing.…”
Section: Introductionmentioning
confidence: 99%